Penerapan Metode Rockport Dalam Tes Kebugaran Jasmani Melalui Aplikasi SIPGAR Pada Usia Produktif - Arisa, Azura; Diaty, Rima (Dedikasi: Jurnal Pengabdian kepada Masyarakat, 2026)
The physical fitness of productive individuals is a crucial determinant in preventing the rise in non-communicable diseases (NCDs) caused by sedentary behavior. The use of digital health technologies such as the SIPGAR app, combined with the Rockport Fitness Walking Test, offers a practical approach to measuring aerobic capacity (VO₂max). This community service activity aims to test the effectiveness of the app-based Rockport method in improving fitness while promoting digital health literacy. The implementation method was conducted directly in a green open space, involving 15 participants aged 15–50 years through a basic medical check-up, PAR-Q screening, and a 1.6 km Rockport test. The results showed a significant increase in VO₂max from 28.4 to 32.1 ml/kg/min (p=0.001), indicating improved cardiorespiratory capacity. Furthermore, 67% of participants were able to operate the app independently, reflecting a good level of functional digital literacy. In conclusion, the integration of the Rockport method with the SIPGAR app effectively improves physical fitness while strengthening community independence in continuously monitoring digital health.